2021
DOI: 10.3889/oamjms.2021.7063
|View full text |Cite
|
Sign up to set email alerts
|

Protective Potential of Ginseng and/or Coenzyme Q10 on Doxorubicin-induced Testicular and Hepatic Toxicity in Rats

Abstract: Introduction: Although doxorubicin (DOX) is a successful cancer chemotherapeutic, side effects limit the clinical utility of DOX-based therapy, including male infertility and hepatotoxicity. Objective: To evaluate the testicular and hepatoprotective effect of ginseng and/or coenzyme Q10 (CoQ10) in rats exposed to DOX and the possible underlying mechanisms. Materials and Methods:  Fifty adult male albino rats were divided into (10/group), control, DOX group, DOX/Gin group, DOX/CoQ10 group and DOX/Gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…Nrf2 is also one of the main modulators of apoptosis, causing a reduction in apoptosis by activating the expression of Bcl-2, down regulating Bax and reducing caspases-3 activity (Niture and Jaiswal, 2012; Niture and Jaiswal, 2013; Renu and Valsala-Gopalakrishnan, 2019). In this study, Dox significantly down regulated the mRNA expression of Nrf2 and HO-1, in agreement with the studies conducted by Ujah et al, (2021) andKhodir et al, (2021), which reported that Dox-induced apoptosis in the testis is associated with decreased expression of Narf2/OH-1. In contrast, co treatment with SeNPs and Dox significantly up regulated the testicular Nrf2/HO-1 pathway.…”
supporting
confidence: 93%
“…Nrf2 is also one of the main modulators of apoptosis, causing a reduction in apoptosis by activating the expression of Bcl-2, down regulating Bax and reducing caspases-3 activity (Niture and Jaiswal, 2012; Niture and Jaiswal, 2013; Renu and Valsala-Gopalakrishnan, 2019). In this study, Dox significantly down regulated the mRNA expression of Nrf2 and HO-1, in agreement with the studies conducted by Ujah et al, (2021) andKhodir et al, (2021), which reported that Dox-induced apoptosis in the testis is associated with decreased expression of Narf2/OH-1. In contrast, co treatment with SeNPs and Dox significantly up regulated the testicular Nrf2/HO-1 pathway.…”
supporting
confidence: 93%
“…For instance, Q10 has been used to suppress cisplatin-mediated oxidative stress which induces inflammation, necrosis, and apoptosis in renal tissue via its antioxidant activities [15]. Similarly, Q10 has been used to alleviate toxicity of anthracycline, tamoxifen, and doxorubicin [16][17][18]. Here, we explored P and Q10 as protective agents against inflammation and oxidative stress induced by CP.…”
Section: Introductionmentioning
confidence: 99%